Mild neoterminal ileal post‐operative recurrence of Crohn's disease conveys higher risk for severe endoscopic disease progression than isolated anastomotic lesions. Issue 9 (14th March 2022) - Bachour, Salam P.; Shah, Ravi S.; Lyu, Ruishen; Rieder, Florian; Qazi, Taha; Lashner, Bret; Achkar, Jean Paul; Philpott, Jessica; Barnes, Edward L.; Axelrad, Jordan; Holubar, Stefan D.; Lightner, Amy L.; et al.
Summary: There are conflicting data assessing the impact of isolated post‐operative anastomotic inflammation on future disease progression. The aim of this study was to determine the relative risk of severe disease progression in post‐operative Crohn's disease (CD) patients with isolated anastomotic disease. Methods: Retrospective cohort study of adult CD patients undergoing ileocolonic resection between 2009 and 2020. Patients with a post‐operative ileocolonoscopy ≤18 months from surgery and ≥1 subsequent ileocolonoscopy were included. Disease activity was assessed using the modified Rutgeerts' score (RS). Primary outcome was severe endoscopic progression, defined as i3 or i4 disease, on immediate subsequent ileocolonoscopy and during entire post‐operative follow‐up. Secondary outcome was surgical recurrence. Results: One hundred and ninety‐nine CD patients had an ileocolonoscopy ≤18 months from surgery, index RS of i0‐i2b and ≥1 subsequent ileocolonoscopy. At index ileocolonoscopy, 34.7% had i0 disease, 16.1% i1, 24.6% i2a and 24.6% i2b. On multivariable logistic regression, i2b disease was associated with severe endoscopic progression compared to i0 or i1 (aOR 5.53; P  < 0.001) and i2a disease patients (aOR 2.63; P  = 0.03). However, i2a disease did not confer increased risk compared to i0 or i1 disease ( P  = 0.09). Furthermore, i2b patients experienced severe endoscopic progression significantly earlier than i0 or i1 disease (aHR 4.68; P  < 0.001), whereas i2a disease did not differ from i0 or i1 disease ( P  = 0.25). Surgical recurrence was not associated with index RS i0‐i2b ( P  = 0.86). Conclusion: Post‐operative ileal disease recurrence, not isolated anastomotic inflammation, confers increased risk for severe endoscopic disease progression. Location of CD recurrence may impact optimal management strategies. Abstract :